PRACTICALITY AND EFFECTIVINESS OF BILINGUAL COMPUTER-BASED LEARNING MODULE - Alfiriani, Adlia; Hutabri, Ellbert (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2017)
This study was aimed at analyzing the level of practicalities and effectivenees of bilingual computer-based learning module on the topic of word processing software at State Elementary School Percobaan, Padang. The study was quantitative with an experimental method. Findings show that the products which were developed had high level of practicality with the value Kr = 1 (standard of practicality = 0.90). This was conï¬ rmed in the test of scalability which the coefï¬ cient of scalability of Ks = 1 (standard of scalability = 0.60). Based on the effectiveness test in the cognitive domain, from 24 students, 20 of them were completing at the average percentage of 84.44 while 4 students were not. In the psychomotor domain, it was categorized as very good with students obtaining an average grade of 97.29 for each indicator. Therefore, this module is very good to use for learning especially in internasional schools. The research ï¬ndings show give evidence to the teachers to continuously make innovation and it can also be used as a reference to develop modules on other topics. KEPRAKTISAN DAN KEEFEKTIFAN MODUL PEMBELAJARAN BILINGUAL BERBASIS KOMPUTER Penelitian ini bertujuan untuk menganalisis tingkat kepraktisan dan efektivitas dari modul pembelajaran bilingual berbasis komputer pada pokok bahasan perangkat lunak pengolah kata di SD Negeri Percobaan Padang. Bentuk penelitian ini adalah kuantitatif dengan jenis eksperimen. Dari hasil penelitian didapatkan bahwa produk yang dikembangkan sudah sangat praktis dengan nilai Kr = 1 karena di atas syarat kepraktisan 0,90. Hal ini dipertegas dalam uji skalabilitas dimana koeï¬sien skalabilitas atau Ks = 1, angka ini juga sudah memenuhi syarat yakni di atas 0,60. Dari uji efektivitas pada ranah kognitif dari 24 orang siswa terdapat 20 siswa yang tuntas dengan persentase rata-rata 84,44. Untuk ranah psikomotor dikategorikan sangat baik dengan angka rata-rata yang diperoleh siswa pada setiap indikatornya yaitu 97,29. Dengan demikian, modul ini sangat baik digunakan dalam pembelajaran khususnya pada sekolah bertaraf internasional. Hasil penelitian memberikan gambaran kepada guru-guru untuk selalu melakukan inovasi dan dapat digunakan guru sebagai acuan untuk pengembangan modul pada pokok bahasan lainnya